An aldol - Bislactonization route to α-methylene bis-γ-butyrolactones - Jittiwud Lertvorachon (2018)
The syntheses of α-methylene γ-butyrolactones and α-methylene bis- γ-butyrolactones are made simple through the use of the versatile dimethyl itaconate - anthracene adduct, 1.